Novel H7N9 influenza immunogen design enhances mobilization of seasonal influenza T cell memory in H3N2 pre-immune mice. Issue 4 (30th November 2022) - Moise, Leonard; Meyers, Lauren M.; Jang, Hyesun; Grizotte-Lake, Mayara; Boyle, Christine M.; McGonnigal, Bethany; Ge, Pan; Ross, Ted M.; De Groot, Anne S.
ABSTRACT: Strategies that improve influenza vaccine immunogenicity are critical for the development of vaccines for pandemic preparedness. Hemagglutinin (HA)-specific CD4 + T cell epitopes support protective B cell responses against seasonal influenza. However, in the case of avian H7N9, which poses a pandemic threat, HA elicits only weak neutralizing antibody responses in infection and vaccination without adjuvant. We hypothesized that an immune-engineered H7N9 HA incorporating a broadly reactive H3N2 HA-specific memory CD4 + T cell epitope that replaces a regulatory T cell-inducing epitope at the corresponding position in H7N9 HA could harness preexisting influenza T cell immunity to increase CD4 + T cells that are needed for protective antibody development. We designed and produced a virus-like particle (VLP) vaccine that carries the epitope augmented H7N9 HA (OPT1) and immunized HLA-DR3 transgenic mice with established H3N2 immunity. OPT1-VLPs stimulated higher stem cell, central, and effector memory CD4 + T cell levels over wild type VLP immunization. In addition, activated, IL-21-producing follicular helper T cell frequencies were enhanced. This novel immunogen design strategy illustrates that site-specific modifications aimed to augment T cell epitope content enhance CD4 + T cell responses among critical subpopulations capable of aiding protective immune responses upon antigen re-encounter and that mobilization of immune memory can be used to overcome the poor immunogenicity of avian influenza viruses.